Pengaruh Akuntabilitas, Transparansi, Pengetahuan Dan Religiusitas Pada Minat Pelaku Umkm Dalam Membayar Zakat Melalui Badan Amil Zakat Kota Bengkulu - Ramah Della Putri; Abdullah Abdullah (Journal of Economic, Bussines and Accounting (COSTING), 2024)
This study aims to determine accountability, transparency, knowledge and religiosity on the interest of Micro, Small and Medium Enterprises to pay zakat through BAZNAS Bengkulu City. The population in this study are Micro, Small and Medium Enterprises who live in Bengkulu City, data collection is done through distributing questionnaires with a sample size of 100 respondents using the slovin formula with predetermined criteria.This research method uses quantitative methods, the data is analyzed using validity, reliability, classical assumptions, multiple linear regression analysis, hypothesis testing and the coefficient of determination (using SPSS 26. The results of this study indicate accountability, and transparency have a positive effect on the interest of MSME actors to pay zakat through BAZNAS Bengkulu City while knowledge and religiosity have no effect on the interest of MSME actors to pay zakat through BAZNAS Bengkulu City. In practical terms, the findings of this study are expected to be useful for BAZNAS Bengkulu City to be taken into consideration as a basis for decision making for BAZNAS Bengkulu City in maximizing zakat revenue from MSME players. Keywords: Accountability, Transparency, Knowledge, Religiosity, Interest, Zakat